(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
Vitiligo is a common acquired depigmentation disorder characterized by the loss of functional skin and mucosal melanocytes the reported incidence is 0.5% to 2% worldwide. Its pathogenesis is mostly consider autoimmune and this pigmentary disorder is strongly associated with autoimmune thyroid disorders. To evaluate the serum thyroid hormone in vitiligo patients of Al-Anbar governorate and to compare the results with other external studies. The study group included 80 patients with vitiligo, and 40 healthy volunteers. Blood thyroid hormone was determined using Monobind kits from reliable USA company. Their ages ranged form 1 to 70 years. Family history of vitiligo was positive in a percentage of (30%) of the patients. The mean levels of serum thyroid hormone (T3, T4) in patients with vitiligo were found to be no significant difference than those of healthy individuals. The TSH level in patient with vitiligo were found to be significantly higher than those of healthy individuals. This study strengthens the relationship between the thyroid hormones intake, formation, and metabolism with the pathogenesis of vitiligo. Therefore it is concluded that vitiligo patients should be evaluated for thyroid hormones.